(untitled) (The Macau Ricci Institute Journal, 2020)
This paper concentrates on the endeavour of the Bishops’ Conference of Laos to expand the Thomist definition of “martyrdom” to make it relevant for their social, religious and political context. In that way, they hoped, the beatification of those whose deaths (1954-70) are attributed to the predecessors of the present-day regime could be understood and accepted by Laotian people of all faiths and affiliations and their political leaders, and could facilitate rather than inhibit social and interreligious dialogue. They asked: While the traditional crucial underpinning of martyrdom is “Odium Fidei,”, is there a deeper understanding of this same mystery, which can be usefully applied in our context? Their reasoning, leading to the beatification in 2016, rests on four major points: – Acknowledge the local objections to a one-sided Western notion of martyrdom; – Focus on the notion of “ancestors” (of the faith), as a basis for mutual understanding; – Define “beatification” as elevating the most meritorious members to the rank of ancestors for the community to remember, venerate and imitate; – Acknowledge Buddhist teachings on the contemplation of death to overcome the deep-seated Laotian aversion toward those who have died a violent death. MARTYRS OF LAOS: FROM “ODIUM FIDEI”1 TO VENERATION OF ANCESTORS After unsuccessful attempts by Jesuits in previous centuries, Christianity, especially in its Catholic form, gained a foothold in Laos at the turn of the 19th and 20th centuries. In the midst of the incessant wars and conflicts of the last century, Laos’ local history has been without much brilliance (Costet, 1999). It suffered a violent backlash in 1975, when the faction supported by international communism took power. Until today, the country has no dioceses, only “missionary circumscriptions” from where the last European missionary left in 1977 (Jacques, 2018).